The Boy from Boort Remembering Hank Nelson - Gammage, Bill; V. Lal, Brij; Daws, Gavan (ANU Press, 2014)
Hank Nelson was an academic, film-maker, teacher, graduate supervisor and university administrator. His career at The Australian National University (ANU) spanned almost 40 years of notable accomplishment in expanding and deepening our understanding of the history and politics of Papua New Guinea, the experience of Australian soldiers at war, bush schools and much else. This book is a highly readable tribute to him, written by those who knew him well, including his students, and also contains wide-ranging works by Hank himself. -Professor Stewart Firth, ANU.